PERMAINAN TRADISIONAL SEBAGAI MEDIA PELESTARIAN BUDAYA DAN PENANAMAN NILAI KARAKTER BANGSA - I Gusti Agung Jaya Suryawan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2018)
Game activities that can develop the psychological aspects of the child can be used as a learning tool in preparation for the adult world. Traditional gameplay is an intergenerational heritage that has a symbolic meaning behind movement, speech, and tools used. These messages are useful for the cognitive, emotional and social development of children as a preparation or means of learning toward life in adulthood. The rapid development of electronic games makes the position of traditional games increasingly eroded and almost unknown. The traditional game of the child is one form of folklore in the form of which circulates orally among certain collective members, traditionally inherited and inherited, and many have variations. Since it includes folklore, the nature or characteristics of the child’s traditional game is old age, unknown to its origin, who it is and where it came from. Traditional games are usually spread by word of mouth and sometimes experience a change in name or form even though they are essentially the same. In relation to character education, the family has a considerable share, because starting from where the planting of moral values can be developed so that juvenile delinquency problems can be avoided. Broadly speaking, character education aims to guide children toward maturity so that children can get a balance between sense and cultural sense and can realize the balance in the future. Therefore, a certain step that can be taken by parents that is, able to provide a positive stimulus and fun to his son, one of them through the traditional game. The traditional permanent development as a vehicle for educating a pleasant character is not so difficult.